IMPLEMENTATION OF UNGKEA BEACH TOURISM OBJECT DEVELOPMENT POLICY AT THE TOURISM OFFICE OF NORTH MOROWALI DISTRICT - Lo’onu, Astati; Ambo, Nuraisyah; Nur Alamsyah, Muh; Nuraisyah, Nuraisyah (Penerbit Lafadz Jaya, 2024)
Tourism is one of the important sectors in Indonesia which has a strategic role in increasing the country's foreign exchange. This is stated in Law Number 10 of 2009 concerning Tourism, which states that: the implementation of tourism is aimed at increasing national income in order to improve the welfare and prosperity of the people, expand and equalize business opportunities and employment opportunities, encourage regional development, introduce and utilize the tourism objects and attractiveness of tourism objects in Indonesia, as well as fostering a sense of love for the country and strengthening friendship between nations. Tourism activities can create demand for consumption and investment, which in turn will give rise to activities for the production of goods and services. So that developing tourism potential becomes one of the superior programs of regional governments, including North Morowali Regency. One of the roles of the government as an agent that accelerates the development of regional potential is to build and develop tourism potential. One concrete way of the regional government of North Morowali district in accelerating the development of regional potential in the tourism sector is by making derivative policies, namely North Morowali regional regulation No. 8 of 2021 concerning the Implementation of Tourism, and North Morowali Regent's Regulation No. 24 of 2023 concerning implementing regulations for North Morowali regional regulations, regarding Tourism Implementation. To find out why the implementation of the Ungkea Beach tourism development policy at the North Morowali Regency Tourism Office was not effective, then researchers used the theory of Donald Van Metter and Carl Van Horn, to look at aspects (standards, measures of objectives and policies, resources, characteristics of implementing agents, attitudes/tendencies, communication between implementing organizations and implementing activities, and the economic, social and political environment). Data collection methods are carried out through observation, direct interviews and documentation. The informant selection technique uses a purposive technique. From the results of the implementation of the Ungkea Beach tourist attraction policy, it has not been effective. This is because there are still shortcomings in several aspects. Among them are the resources referred to in this case are human resources which are still limited, and secondly, financial and other supporting infrastructure in the process of implementing the policy for developing the Ungkea Beach tourist attraction at the North Morowali district Tourism Office.